Variability of urinary concentrations of phthalate metabolites during pregnancy in first morning voids and pooled samples - Hyeong-Moo Shin; Deborah H. Bennett; Jacqueline Barkoski; Xiaoyun Ye; Antonia M. Calafat; Daniel Tancredi; Irva Hertz-Picciotto (Environment International, 2019)
Background: Because phthalates are quickly metabolized and excreted in urine, and human exposures tend to be episodic, phthalate metabolite concentrations measured in a maternal spot urine sample are only indicative of recent exposure. Objective: To examine temporal variability of pregnant women's phthalate exposure using multiple first morning voids (FMV) and pooled samples. Methods: We quantified 14 metabolites of eight phthalates in 577 urine samples collected from 188 pregnancies in the MARBLES (Markers of Autism Risk in Babies – Learning Early Signs) study. We calculated intraclass correlation coefficients (ICCs) using two samples of the same urine type (i.e., two FMVs or two pools) collected across the 2nd and 3rd trimesters. We also calculated ICCs and FMV/pool concentration ratios using two samples (i.e., two FMVs or one FMV and one pool) collected within the same trimester. Results: Overall, ICCs were higher in pooled samples (0.24–0.87) than in FMVs (0.08–0.69). Regardless of the sample type, ICCs tended to be higher for metabolites for which exposure sources are personal care products or indoor residential materials than those for which diet is an important exposure source. ICCs tended to increase and FMV/pool ratios tended to decrease with an increasing number of composite samples in the pools. Conclusions: Our study helped determine the number of samples needed to capture moderate to high reproducibility of individual's average exposure to phthalates and the average exposure can be differently characterized depending on the number of samples in the pools. Keywords: First morning void, Intraclass coefficient, Phthalate exposure, Pooled sample, Variability